Some Hg(II) Complexes with Tetradentate Schiff Base Ligands - Srivastava, Shekhar; Mishra, Richra (Asian Journal of Chemistry, 2010)
Sixteen complexes of Hg(II) of the type HgX2 · SB (where X = Cl– or NO–3; SB = tetradentate aromatic Schiff base ligands derived from diamines and glyoxal; 2,3-butanedione; acetylacetone and 1-phenylbutane- 1, 3-dione) have been synthesised and characterised by elemental analysis, conductivity, IR and XPS data.